PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) RUMAH SAKIT PERTAMINA CIREBON - Sumarsana, Asep; Trisnawati, Iis; Supriana, Nana; Supriyadi, Agung (Jurnal EBI, 2024)
This research aims to determine the influence of autocratic leadership style and work motivation on Organizational Citizenship Behavior (OCB) at Pertamina Hospital Cirebon Distribution.Respondents in this study were employees of Pertamina Hospital Cirebon Distribution using multiple linear regression methods and SPSS analysis tools.The results of this research show that autocratic leadership style influences Organizational Citizenship Behavior (OCB) and work motivation also influences Organizational Citizenship Behavior (OCB).